Effects of biochar, dual inhibitor, and straw return on maize yield, soil physicochemical properties, and microbial system under fertilization conditions - Wei, Zhanbo; Han, Xiaori; Wang, Yonghuan; Zhang, Lili; Gong, Ping; Shi, Yuanliang (Frontiers in Microbiology, 2025)
IntroductionAlthough fertilizers play an important role in achieving high crop yields, improper nitrogen management and application measures have led to a series of ecological and environmental problems. Optimizing fertilization practices in agriculture is crucial for enhancing crop productivity while ensuring sustainable food production.MethodsThis study aims to explore the effects of different fertilization regimes on crop yield, soil physicochemical properties, and microbial ecosystems. During the maize planting process, five fertilization treatments were applied: no fertilizer (CK); conventional fertilization (U), conventional fertilization with composite biochar (UB), conventional fertilization with urease/nitrification inhibitors (UI/NI), and conventional fertilization with straw return (UST).ResultsThe results indicate that maize yield under UI/NI treatment was higher than that under U treatment. The microbial community composition among the fertilization treatments had the same dominant species, but the relative abundance of species varied depending on the fertilization treatment; UB and UI/NI enhanced the role of dominant bacterial populations in the soil, while the UST treatment led to the formation of larger and more complex networks of soil bacterial communities.DiscussionThis study provides scientific and theoretical support for the development and promotion of rational fertilizer application.